Field trials of the prototype Pounder Rig, Uganda, 20th August - 13th November 1999. - Ball, Peter D.; Danert, Kerstin (Cranfield University, 1999)
A prototype low-cost drilling rig was imported to Uganda in August 1999 and handed over to Mpigi District Government. Field trials of this machine were undertaken between 20 th August and 13 th November 1999. This work was enabled through a tripartite Memorandum of Understanding between the Cranfield University/DFID Low Cost well Drilling Project, the Directorate of Water Development (DWD) of the Government of Uganda, and the local Government of Mpigi District. A total of fourteen holes were drilled in a range of geological formations, and six of these were equipped with U3 handpumps installed by the direct install method (screen directly attached below pump cylinder, with rising main doubling as well casing). Of these six, one gave inadequate yield, while the other five were put into use as community water supply wells. The trial of the prototype Pounder Rig offered much opportunity to learn about its capability, the practicalities of well construction by the direct install procedure, and the acceptability of the technology to the Ugandan crew. A full design review followed the field trials, and this is reported under separate cover. A number of practical issues arose during this period, including methods of crew payment, funding of trials, logistics, and conflicts between the requirements of drilling trials and the expectations of rural communities. These were addressed as they arose, but with the benefit of hindsight they could no doubt have been resolved in better ways.